Right ventricle dysfunction assessment for transcatheter tricuspid valve repair: A matter of debate. (26th July 2021) - Preda, Alberto; Melillo, Francesco; Liberale, Luca; Montecucco, Fabrizio; Agricola, Eustachio
Abstract: Newer approaches in transcatheter tricuspid valve replacement (TTVR) have recently showed optimistic data of efficacy and safety in patients at high risk for surgery. However, the absence of residual regurgitation (and subsequently higher likelihood for developing afterload mismatch) with TTVR compared with transcatheter tricuspid valve intervention may become a critical concern if RV dysfunction is misdiagnosed. Indeed, such sudden increase in afterload on the right ventricle (RV) may not be tolerable, resulting in higher risk of acute right heart failure in the early postoperative period. In this context, strain imaging may find a further application to provide a more comprehensive stratification of the severity of RV dysfunction and thus help to better define the eligibility criteria and timing for TTVR. Meanwhile, it is of paramount importance to underline the contribution given by the Trivalve study on the understanding of the role of RV function in TTVI, that so far was largely undefined, being evaluated only in small noncontrolled cohorts.